(untitled) (Sainmatika: Jurnal Ilmiah Matematika dan Ilmu Pengetahuan Alam, 2026)
This study aims to evaluate the effect of various dosages of Arbuscular Mycorrhizal Fungi (AMF) on the growth of oil palm (Elaeis guineensis Jacq) seedlings during the nursery phase. The FMA treatments consisted of 5 grams, 12.5 grams, 15 grams, 17.5 grams, and 20 grams, alongside a control group without AMF application. Key observed variables included plant height, leaf length, leaf width, leaf count, and phosphorus (P) availability in the growing medium over a one-month period. The results demonstrated that AMF application significantly enhanced plant height, leaf length, leaf number, and phosphorus availability in the medium. The 20-gram AMF dosage yielded the most favorable outcomes, with average plant height reaching 22.2 cm by the fourth week and phosphorus availability peaking at 1209.75 ppm—substantially higher than the control group. However, leaf width did not exhibit a significant increase during the observation period, likely due to genetic and environmental factors. In conclusion, optimal AMF dosages (15–20 grams) effectively promote vegetative growth of oil palm seedlings and improve phosphorus availability in the growing medium. Therefore, precise AMF application can support sustainable success in oil palm seedling cultivation.